STUNTING REDUCTION STRATEGY IN INDONESIA: MATERNAL KNOWLEDGE ASPECTS - Putri, Prima Maharani; Shafira, Aqilla Shafa; Mahardhika, Gembong Satria (Universitas Airlangga, 2024)
Introduction: Based on an Indonesian Ministry of Health report, the incidence of stunting has decreased from 24.4% in 2021 to 21.6% in 2022. Reducing stunting rates in children is a global nutrition target in 2025. One of the causes of nutritional problems in children is inadequate intake of nutrients according to their nutritional needs. Based on the above explanation, maternal nutritional knowledge and the government’s role are essential in reducing stunting in Indonesia. Aim: The research investigation was aimed at investigating the level of maternal nutritional awareness as well as the government's participation in reducing stunting in children under the age of five. Methods: This quantitative study was an analytical observational design using a cross-sectional study approach. The samples were mothers of children under five carried out using non-probability purposive sampling, while respondents for the stunting intervention program provider used the snowball sampling technique. Data collection was conducted in locations with high prevalence of stunting, comprising two distinct groups of participants. Result: The statistical result using chi-square shows a significant correlation between maternal nutritional knowledge and the government’s role in reducing stunting in children under five, with a p-value (0.000) < α (0.05) and p-value (0.008) < α (0.05). Conclusion: There is a relationship between the level of nutritional knowledge of mothers under five and the role of the government in the incidence of stunting. There is a need for further and multidisciplinary management in stunting cases, especially in Indonesia.